A high-precision bidirectional time-transfer system over a single fiber based on wavelength-division multiplexing and time-division multiplexing - Guo, Xinxing; Liu, Bo; Kong, Weicheng; Quan, Honglei; Zhang, Yucan; Liu, Tao; Dong, Ruifang; Zhang, Shougang (Frontiers in Physics, 2023)
In this paper, a high-precision bidirectional time transfer system over a single fiber based on wavelength division multiplexing and time division multiplexing (SFWDM-TDM) is proposed, which combines the advantages of wavelength division multiplexing and time division multiplexing. It uses two dense wavelength division channels to effectively suppress the problem of optical fiber reflection. At the same time, the time division multiplexing method is used in combination with sampling and holding the time to complete the multi-user task. In the hardware, we optimized the carrier processing and the high-precision time delay control module of the SFWDM-TDM system to complete high-precision time transfer equipment. In the software and algorithm, the optical fiber time interval measurement method and measurement times are optimized, and the SFWDM-TDM system reaches synchronization accuracy of 8.9 ps at 1s. Finally, a real-time detection mechanism with self-recovery ability is added to the system. It will lay the foundation for a reliable, long-distance, high-precision and multi-user mode optical fiber time and frequency transfer network.